Ascophyllum nodosum and Fucus vesiculosus ameliorate restenosis via improving inflammation and regulating the PTEN/PI3K/AKT signaling pathway - Crystal Ngofi Zumbi; Chun-Hsu Pan; Hui-Yu Huang; Chieh-Hsi Wu (Food Science and Human Wellness)
Restenosis is a common complication following coronary angioplasty. The traditional use of seaweeds for health benefits has increasingly been explored, however few studies exist reporting its protective effects on the development of restenosis and gut dysbiosis. The aim of this study was to investigate the potential of seaweed extracts (SE) of Ascophyllum nodosum and Fucus vesiculosus in inhibiting intimal hyperplasia in a rat model of restenosis and its underlying mechanisms in macrophages and vascular smooth muscle cells (vSMCs). 16S rRNA sequencing was done to investigate the regulatory effect of SE on the gut microbiome of injured rats. As indicated by the results, SE significantly inhibited the progression of intimal hyperplasia in vivo, attenuated inflammation in macrophages and could inhibit the proliferation, dedifferentiation and migration of vSMCs. It was observed through immunoblotting assays that treatment with SE significantly upregulated PTEN expression in macrophages and inhibited the upregulation of PI3K and AKT expression in vSMCs. Meanwhile, according to the 16S rRNA gene sequencing analysis, supplementation with SE modulated gut microbiota composition in injured rats. In conclusion, SE could ameliorate intimal hyperplasia by inhibiting inflammation and vSMCs proliferation through the regulation of the PTEN/PI3K/AKT pathway and modulating the gut microbiome.